Corporate Governance in Acquisitions : Opportunities and Challenges - Mohamad Chaidir; Benardi Benardi; Seger Santoso (Cahaya Abadi Publisher, 2024)
This study aims to analyze the role of acquisitions in corporate governance transfer, focusing on the impact of governance gaps between the acquiring and target companies before the acquisition. Through a qualitative literature review, this research identifies that the existing governance gaps can affect the success of post-acquisition integration and its impact on the long-term performance of the acquired company. Previous studies have shown that acquisitions can provide an opportunity to improve corporate governance practices; however, their success heavily depends on managing the governance differences between the two entities. Additionally, factors such as organizational culture, managerial readiness, and communication policies also play a significant role in facilitating effective governance transfer. The conclusion of this study is that although acquisitions can offer benefits in terms of governance transfer, managing governance gaps effectively is crucial to achieving optimal outcomes. This research contributes to the understanding of governance transfer dynamics in the context of acquisitions and provides insights for practitioners and policymakers involved in the corporate acquisition process.